Hsa_circ_0001492 regulates the hsa-miR-145-5p/ovarian carcinoma immunoreactive antigen domain 2 axis to promote the progression of lung adenocarcinoma - Yuanqiang He; Gang Li; Ran Fu; Yue Li; Ying Wang (Biomolecules & Biomedicine)
Circular RNA (circRNA) has been proven to be a key regulator in a range of tumor illnesses, such as lung adenocarcinoma (LUAD); however, the regulatory mechanisms of circRNA remain unclear. In this study, circRNA (hsa_circ_0001492) in LUAD was examined for its regulatory and functional potential. qRT-PCR was used to assess the hsa_circ_0001492 level in LUAD. The RNAse R digestion test was employed to isolate hsa_circ_0001492. The primary location of hsa_circ_0001492 enrichment in LUAD cells was identified through a nucleoplasmic separation test. LUAD cell migration, proliferation, and spherogenicity were examined using wound healing, transwell, EdU, and cell spherogenicity assays. The association between miR-145-5p and hsa_circ_0001492/ovarian carcinoma immunoreactive antigen domain 2 (OCIAD2) was validated using a dual luciferase experiment. The interaction between sh-hsa_circ_0001492 and miR-145-5p was confirmed through an RNA pull-down assay. The effects of hsa_circ_0001492, miR-145-5p, and OCIAD2 on LUAD tumor development were examined using xenograft mouse models and immunohistochemistry tests. Results showed a higher amount of hsa_circ_0001492 in LUAD. The cytoplasm of LUAD cells was observed in the area where hsa_circ_0001492 mainly accumulated; hsa_circ_0001492 enhanced LUAD cell migration, proliferation, and sphere-forming ability. MiR-145-5p and OCIAD2 were identified as targets of hsa_circ_0001492 and miR-145-5p, respectively. The level of OCIAD2 was increased by hsa_circ_0001492 through targeted binding to miR-145-5p. In nude mice, tumor growth was inhibited by silencing hsa_circ_0001492, while knockdown of miR-145-5p and overexpression of OCIAD2 promoted the growth of LUAD tumors. In conclusion, hsa_circ_0001492 regulates the hsa-miR-145-5p/OCIAD2 axis to promote the progression of LUAD, and could be a useful target for the diagnosis and treatment of LUAD.